The outcomes of residual ametropia correction by LASIK and PRK on pseudophakic eyes depending on IOL model - E.P. Gurmizov; K.B. Pershin; N.F. Pashinova; A.Yu. Tsygankov (РМЖ "Клиническая офтальмология")
Background: multiple studies discuss safety and predictability of laser refractive surgery to correct residual ametropia after IOL implantation. Considering few large comparative studies on ametropia correction by LASIK and photorefractive keratectomy (PRK), we have performed a literature search in Russian and English databases throughout the time of existence of laser refractive surgery (about 20 years). Aim: to analyze the outcomes of residual ametropia correction by LASIK and PRK on pseudophakic eyes depending on IOL model. Patients and Methods: 57 patients (77 eyes) after cataract surgery (n=37) or refractive lens exchange (n=40) were enrolled in this prospective open study. 45.6% were women and 54.5% were men. Mean age was 50.8±13.9 years. LASIK (n=70, 91.1%) and PRK (n=7, 8.9%) were performed using standard protocols. Postoperatively, all patients were prescribed with hyaluronic acid-containing eye drops Ocutears®. In most patients (97.5%), target refraction was ±0.25 D. Spherical and aspherical monofocal IOLs were implanted on 38 eyes (group I),multifocal IOLs were implanted on 39 eyes (group II). The groups were similar in all parameters (p>0.05) excepting cylindrical component (-1.45±0.43 D in group I and -0.4±0.29 D in group II, p=0.046). Follow-up was 6 to 9 months. Results: in group I, uncorrected visual acuity (UCVA) significantly improved from 0.31±0.14 to 0.72±0.22 (p < 0.05). Target refraction ±0.5 D was achieved in 81.6% of patients (n=31). After 6 months, cylindrical component significantly reduced from -1.45±0.43 D to -0.18±0.80 D. In group II, UCVA significantly improved from 0.43±0.17 to 0.80±0.18 (p<0.05). Target refraction was achieved in 82.1% of patients (n=32). Conclusion: residual ametropia after IOL implantation can be corrected by LASIK and PRK. Procedure efficacy in terms of target refraction achievement was independent of IOL model. The differences were demonstrated for cylindrical component only. The rates of target refraction achievement were similar in the groups. Keywords: pseudophakia, LASIK, PRK, femtoLASIK, correction, residual ametropia, Ocutears. For citation: Gurmizov E.P., Pershin K.B., Pashinova N.F., Tsygankov A.Yu. The outcomes of residual ametropia correction by LASIK and PRK on pseudophakic eyes depending on IOL model. Russian Journal of Clinical Ophthalmology. 2019;19(2):67–72.